Принципы обучения языку специальности армяноязычных студентов-бакалавров - Ходжумян, Белла
The article is devoted to the problem of teaching the specialty language of bachelor Armenian – speaking students of natural faculties in the Russian language lessons. In order to effectively organize lessons on the specialty The Department of the Russian language (for natural faculties) have been developed special manuals for specific specialties, based on the modern methodology of teaching the language of specialty and saturated with the necessary lexical and grammar assignments and texts on the specialty. Special terminology dictionaries also help to learn the language of the specialty.In the preparation of students for the future specialty plays an important role familiar with the methods of scientific work, as well as extracurricular work. Հոդվածում ներկայացված են բակալավրիատի հայալեզու ուսանողներին մասնագիտական լեզվի ուսուցանման հիմնական սկզբունքները: Այդ գործընթացը ապահովվում է ուսումնական մասնագիտական ձեռնարկների և տերմինաբանական բառարանների միջոցով: Կարևոր է նաև ուսանողներին ծանոթացնել գիտական աշխատանքի մեթոդների հետ, սովորեցնել գրել ռեֆերատներ, կուրսային և ավարտական աշխատանքներ, կազմել ամփոփագրեր: Ապագա մասնագետների պատրաստման գործում մեծ դեր է խաղում նաև արտալսարանային աշխատանքը՝ ուսանողական գիտաժողովներ և մասնագիտական վիկտորինաներ:
Keywords: Методика